'The way I understood it, it wasn't meant to be understood' – when 6th grade reads Franz Kafka. Issue 5 (3rd September 2017) - Johansen, Martin Blok
Abstract: In recent years, literacy problematics and different concepts (Cooperative Learning, Learning Styles) have taken up much of the school's literature teaching. It has pushed discussions of the professional content into the background. This article takes up the content discussion for renewed debate, but now also with the aim of discussing the literary texts one can present to children in school. The research questions posed are: Which texts can justifiably be presented to children as part of teaching in school? What will happen if 10 to 12-year-old Danish school pupils are presented with classical and canonized texts by authors like Kafka, Proust and Dostoyevsky? How will they react? How will they read the texts? The point of departure for the article is an observational and interview study of a Danish 6th grade's reading and analysis of classical and canonized adult literature. The study takes its starting point in three concepts rooted in theory, i.e. unpredictability, defamiliarization and entitlement, which are subsequently used to get to grips with the empirical part of the study. The article does not attempt to depict a hard-and-fast picture of all children being equally enthusiastic about the new texts. Instead it presents a picture of a class in which lively literary conversations are conducted. And irrespective of whether the child is one of those who enjoys the texts, whether the children are irritated, challenged or provoked by them, they are never experienced as trivial or irrelevant.